Optimizing Polymer Composites for Effective Electromagnetic Shielding: The Role of Carbon Filler Properties and Temperature - Lijun Huang; Aleksey Kudryavtsev; Olga Moskalyuk; Ruixuan Zhang; Nasir Ali; Muhammad Bilal Ghori; Huizhu Hu; Ekaterina Gushina; Anna Stepashkina (Advanced Electronic Materials)
Abstract Polymer composites with carbon nanofillers are promising for electromagnetic shielding, with performance influenced by filler geometry, orientation, and temperature. Spherical carbon black enhances scattering, while anisotropic carbon nanotubes (CNTs) exhibit directional wave propagation and polarization. CNT orientation significantly affects the shielding efficiency, with the perpendicular alignment outperforming the parallel alignment. Temperature‐dependent CNT polarization further underscores the need for thermal considerations in material design.